INOVASI PEMBELAJARAN DI ERA DIGITAL SEBAGAI UPAYA MENINGKATKAN KUALITAS PENDIDIKAN BAGI SISWA - Nuraeni; Muhammad Ali; Putri Salzabila; Nurul Bahari; Ahmad Fadil Zuhair; Muhammad Danil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe learning innovation in the digital era as an effort to improve the quality of education for students. The development of information and communication technology has brought significant changes to the field of education, particularly in creating more interactive, effective, and flexible learning processes. Digital learning innovation is implemented through the use of technology-based learning media, such as e-learning platforms, learning applications, interactive videos, and the internet as a learning resource. The research employed a qualitative approach using a descriptive method. Data were collected through literature studies and observations of the implementation of digital learning in educational environments. The results of the study indicate that learning innovation in the digital era is capable of increasing students’ learning motivation, creativity, active participation, and critical thinking skills. In addition, the use of technology in learning also helps teachers deliver materials in a more engaging and efficient manner. Therefore, digital learning innovation has become an important strategy in improving the quality of education in accordance with the demands of modern developments.